2007
DOI: 10.1007/s11119-007-9039-8
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific potassium application based on the fertilizer potassium availability index of soil

Abstract: Soil varies in its potassium (K + ) content and ability to supply K + to crops. Site-specific K + management aims to optimize crop production and minimize K + loss from the soil. The spatial variation of available K + prior to fertilizer application, the K + fixation capacity of soil and soil texture need to be taken into account for variable-rate K + application. This study was done to measure the spatial variation of the fertilizer K + availability index (A I ), which shows the potential for K + fixation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Plants can take up K only from the soil solution and its availability is dependent upon the K dynamics as well as on total K content. K is present in soil in four main forms (Jalali, 2007). These are: (i) water soluble K (solution K) which is dissolved in the soil solution; (ii) exchangeable K is the form that is electrostatically retained by negatively charged soil colloids (clays, organic matter, sesquioxides); (iii) Non-exch-K is temporarily trapped between the interlayers of clay minerals (illites,…”
Section: Introductionmentioning
confidence: 99%
“…Plants can take up K only from the soil solution and its availability is dependent upon the K dynamics as well as on total K content. K is present in soil in four main forms (Jalali, 2007). These are: (i) water soluble K (solution K) which is dissolved in the soil solution; (ii) exchangeable K is the form that is electrostatically retained by negatively charged soil colloids (clays, organic matter, sesquioxides); (iii) Non-exch-K is temporarily trapped between the interlayers of clay minerals (illites,…”
Section: Introductionmentioning
confidence: 99%
“…Iho and Laukkanen [5] reported that excessive phosphorus fertilization leads to potential soil-P accumulations and risk of P loss in runoff, negatively impacting the quality of receiving water bodies and precision phosphorus management strategy. Jalali [6] recommended site-specific or variable-rate potassium application based on the fertilizer potassium availability index of soil after grouping the soils into different management zones by a non-hierarchical cluster analysis. The spatial distribution of soil chemical properties is altered by agriculture, particularly by the application of fertilizers, amendments and tillage activities in the upper 10 cm depth of soil, even within a given soil plot [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the rate of K + adsorption on illite and vermiculite was reported to be much slower than montmorillonite and kaolinite (Jalali, 2007, Al-Azawi, 2010. Clay minerals like semictite and kaolinite easily release all of their K + adsorbed than illite and vermiculite (Ghosh and Sing, 2001), upon removal rate by plants and rapidity at which potassium can be desorbed from the adsorbed phase whereas initial adsorption equilibrium solution levels serves as an index of potassium release (Rao et al, 2004, Jalali, 2006 . This equilibrium of potassium concentration appears to provide a better index of soil fertility.…”
Section: Introductionmentioning
confidence: 99%